Can the Presence of Significant Coagulopathy be Useful to Exclude Symptomatic Acute Pulmonary Embolism?. Issue 3 (May 2013) - Ho, K. M.; Tan, J. A.
Thrombocytopaenia or an abnormal coagulation profile is not rare in hospitalised patients who have symptoms consistent with acute pulmonary embolism (PE). Theoretically, coagulopathy is more likely to occur in patients with pneumonia than acute PE. This study aimed to assess whether the presence of coagulopathy could be used to exclude acute PE in patients with symptoms and signs consistent with acute PE. In this study, a significant coagulopathy was defined as a platelet count <100 × 10 9 /l, an international normalised ratio >1.5, or activated partial thromboplastin time >50 seconds. Patients treated with systemic anticoagulants prior to computed tomography pulmonary angiography were excluded. Of the 986 consecutive patients who required computed tomography pulmonary angiography to exclude acute PE over a four-month period in five hospitals in Western Australia, acute PE was confirmed in 149 patients (15.1%). The incidence of coagulopathy was not significantly different between those with and without acute PE (4 vs 7%, respectively; P= 0.161) and between those with and without pneumonia (8 vs 7%, respectively; P=0.505). Positive and negative likelihood ratios of coagulopathy in differentiating acute PE or pneumonia were both unsatisfactory. As a continuous predictor, platelet counts, international normalised ratio, activated partial thromboplastin time and plasma fibrinogen concentrations were also not useful in differentiating between acute PE and other pulmonary pathologies (areas under the receiver operating characteristic curve were all close to 0.5). In conclusion, the presence of significant acquired coagulopathy cannot be used to suggest pneumonia or exclude symptomatic acute PE when the prevalence or pre-test probability of acute PE is not low.